Aplikasi Pemesanan Online Kue Tradisional Berbasis Web Menggunakan Metode Rapid Aplication Development - Wulandari, Fitri; Pramata, Adhitya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Traditional cakes are one of Indonesia's culinary cultural heritages that need to be preserved. However, small business actors, especially MSMEs, often face obstacles in reaching consumers widely due to limited marketing access. This study aims to design and build a website-based traditional cake online ordering application using the Rapid Application Development (RAD) method. This method was chosen because of its iterative approach and direct user involvement, so that application development can be carried out quickly and according to needs. This application is designed to provide key features such as product catalogs, online ordering systems, and digital payments. Web technology is used so that the application can be accessed through various devices, both desktop and mobile. The development process includes four stages: needs planning, design, planning, and implementation. The test results show that the application has achieved a 100% functional success rate, with all key features running smoothly. In addition, User Acceptance Testing (UAT) testing using the Likert scale obtained an average score of 4.5 out of 5, reflecting a very high level of user satisfaction with ease of use, ordering, and product completeness. This application is considered effective in supporting the digitalization of micro, small, and medium enterprises (MSMEs) and preserving local culinary through technological innovation. This application not only makes it easier for consumers to order traditional cakes online, but also helps MSMEs manage orders and expand market reach. This research contributes to supporting the digitalization of MSMEs, especially in the traditional culinary sector, and has the potential to be a solution to maintain the existence of traditional cakes in the digital era.